Review of the Halal Product Guarantee Act Towards the Implementation of Halal Product Legality Registration in Indonesia - Rusmiyati , Kurnia; Syamsul , Mulya; Gumilang Lestari, Ayu (Prodi Ekonomi Syariah Universitas Majalengka, 2024)
The purpose of this study is to analyze how the review of the Halal Product Guarantee Act describes the registration of halal certification products and the obstacles to its implementation based on existing facts. The research method used in this research is the normative juridical method. The results of the study found that halal certification in the Law on Halal Product Guarantee must be intervened by the government in order to maintain the interests of maslahah, especially consumer protection for the halalness of a product, the government is also required as a facilitator, regulator and supervisor.